Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) x*2+x*3=4
x*(2+3)=4
x*5=4
x=4:5
x=4/5(0,8)
Vậy x = 4/5 (0,8)
b)x*9-1,5=30
x*9 = 30+1,5
x*9 = 31,5
x = 31,5 : 9
x = 3,5
Vậy x = 3,5
a) X x 2 + X x 3 = 4 b) X x 9 - 1,5 = 30
X x ( 2 + 3 ) = 4 X x 9 = 30 + 1,5
X x 5 = 4 X x 9 = 31,5
X = 4 : 5 X = 31,5 : 9
X = 0,8 X = 3,5
~ Hok T ~
x . 9 - 1,5 = 30
x . 9 = 30 + 1.5 = 31.5
x = 31.5 : 9 = 3.5
a) 1,5 . x + 15 + x = 31
(1,5 + 1) . x + 15 = 31
2,5 .x = 31 - 15
2,5 - x = 16
x = 2,5 - 16
x = -13,5
b) (x + 1) + (x + 2) + (x + 3) + ( x + 4) + (x + 5) = 45
(x + x + x ....+ x) + (1 + 2 + 3 + 4 + 5) = 45
5x + 15 = 45
5x = 45 - 15
5x = 30
x = 6
a, x*2*3=4 => x=4:3:2 =>x=2/3
b, x*9-1,5=30 =>x*9=31,5=>x=3,5
a) X + 1/4 = 5/8 + 2/5
X + 1/4 = 41/10
X = 41/10 - 1/4
X = 31/40
b) X : 3/4 = 4/10 - 4/10
X : 3/4 = 0
X = 0
c) X + 3,4 x 2,6 = 4,8 x 5,2
X + 8,84 = 24,96
X = 24,96 : 8,84
X = 48/17
d) X : 1,5 + 1,5 = 0,8N x 2
= bó tay nhé
Bài 1:
a; (\(\dfrac{1}{4}\)\(x\) - \(\dfrac{1}{8}\)) x \(\dfrac{3}{4}\) = \(\dfrac{1}{4}\)
\(\dfrac{1}{4}x\) - \(\dfrac{1}{8}\) = \(\dfrac{1}{4}\) : \(\dfrac{3}{4}\)
\(\dfrac{1}{4}\)\(x\) - \(\dfrac{1}{8}\) = \(\dfrac{1}{4}\) x \(\dfrac{4}{3}\)
\(\dfrac{1}{4}x\) - \(\dfrac{1}{8}\) = \(\dfrac{1}{3}\)
\(\dfrac{1}{4}x\) = \(\dfrac{1}{3}\) + \(\dfrac{1}{8}\)
\(\dfrac{1}{4}\) \(x\)= \(\dfrac{8}{24}\) + \(\dfrac{11}{24}\)
\(\dfrac{1}{4}x=\dfrac{11}{24}\)
\(x=\dfrac{11}{24}:\dfrac{1}{4}\)
\(x=\dfrac{11}{24}\times4\)
\(x=\dfrac{11}{6}\)
b; \(\dfrac{12}{5}:x\) = \(\dfrac{14}{3}\) x \(\dfrac{4}{7}\)
\(\dfrac{12}{5}\) : \(x\) = \(\dfrac{8}{3}\)
\(x\) = \(\dfrac{12}{5}\) : \(\dfrac{8}{3}\)
\(x\) = \(\dfrac{12}{5}\) x \(\dfrac{3}{8}\)
\(x\) = \(\dfrac{9}{10}\)
5x - 15 = 50 : 0,25 3,5 - 2 . ( x - 1 ) = 1,5 145 - ( x -13 ) = 45 4x + 30 = 50
5x - 15 = 200 2 . ( x - 1 ) = 3,5 - 1,5 x - 13 = 145 - 45 4x = 50 - 30
5x = 200 + 15 2 . ( x - 1 ) = 2 x - 13 = 100 4x = 20
5x = 215 x - 1 = 2 : 2 x = 100 + 13 x = 20 : 4
x = 215 : 5 x - 1 = 1 x = 113 x = 5
x = 43 x = 1 + 1
x = 2
Nếu đúng k cho mình nhé
a,\(x.2+x.3=4\\\) b,\(x.9-1,5=30\)
\(x\left(2+3\right)=4\) \(x.9=30+1,5=31,5\)
\(x=31,5:9=3,5\)
\(x.5=4=>x=4:5=\frac{4}{5}\)
a, x * 2 + x * 3 = 4
x * ( 2 + 3 ) = 4
x * 5 = 4
x = 4 : 5
x = 4/5
b, x * 9 - 1,5 = 30
x * 9 = 30 + 1,5
x * 9 = 31,5
x = 31,5 : 9
x = 3,5